(untitled) (INNOVATIVE ECONOMY, 2020)
Bachkir I.H. BANKRUPTCY OF THE ENTERPRISE: APPROACHES, PROCEDURES, ASSESSMENT OF PROSPECTS AND PRIORITIES OF MANAGEMENT IN THE CONDITIONS OF SOLVENCY CRISIS Purpose. The aim of the article is defining approaches to the essence of the concept of “bankruptcy”, disclosing the content of the bankruptcy procedure and assessing the prospects and priorities of enterprises in the face of potential threats to their activities. Methodology of research. The following methods are used to achieve this goal: analysis and synthesis ‒ to study scientific research, normative and legal regulations to understand the essence of the concept of “bankruptcy”; statistical analysis ‒ to identify trends that confirm the hypothesis of an increase in the number of bankruptcies in a crisis, based on the indicators of profitability / loss of enterprises of Ukraine for 2016-2020; tabular – for a visual presentation of the analysed statistics. Findings. The concept of “bankruptcy” based on the analysis of the interpretation in the scientific literature revealed two approaches to understanding its essence: classical and market. It is determined that the main preconditions of bankruptcy are: legal grounds and impossibility of settlements, reorganization and conclusion of amicable agreements. It is established that the Bankruptcy Procedure Code of Ukraine defines improved procedures for declaring a debtor bankrupt. It is proved that during the crisis the number of unprofitable enterprises increases, which increases the risks of bankruptcy and confirms the market approach to understanding the essence of bankruptcy. Priorities and prospects of functioning of Ukrainian enterprises in the medium term are revealed. Originality. The study of the essence of the concept of “bankruptcy” and approaches to its interpretation was further developed, which allowed to establish the prevalence of a market approach to its understanding in modern conditions - as a natural mechanism of market economy selection of efficient enterprises in a crisis. It is established that the problem of ensuring income stability will be the main one in the management of Ukrainian companies in the medium term, and the growth of bankruptcies will be typical for the Ukrainian business environment in the next 2-3 years. Therefore, the priorities of the real sector are to reduce the number of insolvent customers and revise agreements to optimize receivables. Practical value. The results of this study may be the basis for further research on the prospects and priorities for overcoming the negative effects of the crisis in the context of combating bankruptcy. Key words: bankruptcy in crisis conditions, solvency crisis, market approach, classical approach.